A Study of Solute-Solvent Interaction of Chloride and Bromide of Barium in Aqueous Dimethyl-formamide (DMF) between 298 and 313 K from Apparent Molal Volume Data. - KUMARI VERMA, POONAM; DHOMNE , V.P.; SINHA, S.C.; SINHA, P.C. (Asian Journal of Chemistry, 2010)
The apparent molal volume φv of chloride and bromide of barium in aqueous dimethyl-formarnide (DMF) of different compositions (10, 20 and 40 wt %) with different concentrations of electrolytes between 298 and 313 K have been determined from densities data. The data have been analysed using Masson's equation. The limiting apparent molal volumes (φvo) and exprimental slopes (sv*) have been interpreted in terms of solute-solvent and solute-solute interactions respectively. The φvo values are found to be positive and increase with the solvent compositions as well as with temperatures for both the electrolytes. The φvo values are higher for barium bromide while Sv* values are higher for barium chloride. sv* values increase with the rise in temperature and decrease with the increase in DMF in the solvent. φvo values for electrolytes are obtained by extrapolation of curves for zero mole-fraction of DMF i.e. for water and they are found to decrease with the rise of temperatures in case of barium bromide. The results have been correlated to the dielectric constant of solvent and viscosity β-coeffiecient of Jone-Dole equation. The results are in good agreement to the conclusions proposed on the basis of thermodynamic parameters of viscous flow obtained from the method of Nightingale and Benck.